Answer:
[tex]y+6=4(x-1)[/tex] or [tex]y-6=4(x-4)[/tex]
Step-by-step explanation:
We want to find the equation in point-slope form of the line that passes through the two points (1, -6) and (4, 6).
Recall that point-slope form is given by:
[tex]y-y_{1}=m(x-x_{1})[/tex]
Where m is the slope.
Find the slope m using the two given points.
[tex]\displaystyle m = \frac{\Delta y}{\Delta x} = \frac{6-(-6)}{4-1} = \frac{12}{3} = 4[/tex]
Substitute. We can use either point. Using the point (1, -6), we acquire:
[tex]y-(-6)=4(x-(1))[/tex]
Simplify:
[tex]y+6=4(x-1)[/tex]
And using the point (4, 6), we acquire:
[tex]y-(6)=4(x-(4))[/tex]
Simplify:
[tex]y-6=4(x-4)[/tex]